Antibacterial activities of the methanol extracts, fractions and compounds from Fagara tessmannii. (1st July 2015) - Tankeo, Simplice B.; Damen, Francois; Awouafack, Maurice D.; Mpetga, James; Tane, Pierre; Eloff, Jacobus N.; Kuete, Victor
Abstract: Ethnopharmacological relevance: Fagara tessmannii is a shrub of the African rainforests used to treat bacterial infections, cancers, swellings and inflammation. In the present study, the methanol extract from the leaves (FTL), bark (FTB), and roots (FTR) of this plant as well as fractions (FTR1-5) and compounds isolated from FTR namely β -sitosterol-3- O-β-d -glucopyranoside (1 ), nitidine chloride (2 ) and buesgenine (3 ), were tested for their antimicrobial activities against a panel of Gram-negative bacteria including multidrug resistant (MDR) phenotypes. Materials and methods: The broth microdilution method was used to determine the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of the above samples; Column chromatography was used for the fractionation and purification of the roots extract whilst the chemical structures of compounds were determined using spectroscopic techniques. Results: Results of the MIC determinations indicated that the crude extracts from the roots as well as fraction FTRa4 were active on all the 26 tested bacterial strains. MIC values below 100 µg/mL were obtained with roots, leaves and bark extract respectively against 30.8%, 15.4% and 11.5% tested bacteria. The lowest MIC value below of 8 µg/mL was obtained with extract from the roots against Escherichia coli MC100 strain. The lowest MIC value of 4 µg/mL was also obtained with compound 3 against E. coli AG102 and Klebsiella pneumoniae ATCC11296 Conclusions: The present study demonstrates that F. tessmannii is a potential source of antimicrobial drugs to fight against MDR bacteria. Benzophenanthrine alkaloids 2 and 3 are the main antibacterial consituents of the roots of the plant. Graphical abstract: The crude extracts from the roots as well as fraction FTRa4 were active on all the 26 tested bacterial strains. MIC values below 100 µg/mL were obtained with roots, leaves and bark extract respectively against 30.8%, 15.4% and 11.5% tested bacteria. β -sitosterol-3- O-β-d -glucopyranoside (1 ) did not show any inhibitory activitiy when it was tested at up to 512 µg/mL. Nitidine chloride (2 ) displayed selective activities whilst buesgenine (3 ) was active on all tested bacteria.